(untitled) (Proceedings of Southern Federal University. Philology, 2021)
DOI 10.18522/1995-0640-2021-3-114-122 The article seeks to explore the concepts of the romantic and the mundane in the works of the American writer Frank Norris (18701902). Basing on the two novels, “Blix” and “McTeague”, the study examines the originality of the writer’s naturalist programme. F. Norris develops a specific understanding of the romantic, viewing it as the characters’ optimistic mood, their willingness to act and change their lives for the better. This is opposed by everyday life – in the form of a familiar routine which inevitably leads to stagnation, a kind of personal catastrophe. Key words: Frank Norris, naturalism, romantic, realism, consumer society, sentimental, the turn of the twentieth century.